ANALISIS PENINGKATAN KUALITAS PELAYANAN MENGGUNAKAN PENDEKATAN E-SERVQUAL, IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN POTENTIAL GAIN CUSTOMER VALUE (PGCV) PADA WEBSITE PT.POS INDONESIA - Safura Mutiara Segonang; Lizar Alfansi; Seprianti Eka Putri (UNIB Press, 2021)
research objectives are to identify the service quality level of PT. Pos Indonesia website and to recognize certain criteria which needs to be improved based on the improvement priority scale in the service quality of PT. Pos Indonesia website. This research was conducted by using E-ServQual method (Electronic Service Quality), Importance Performance Analysis (IPA) and Potential Gain Customer Value (PGCV). The analysis was conducted using 20 items criteria in terms of 6 dimensions included Efficiency, Fullfilment, System availability, Privacy, Responsiveness, and Contact. The data collection method used was questionnaire, which involved the sharing of google forms link through social media to share and collect the questionnaire result. The result of this research showed that the electronic service quality of PT. Pos Indonesia website is in a good category. Generally, the service performance of PT. Pos Indonesia website has meet customers’ expectation, or satisfactory. However, fulfillment dimension still has a negative gap. On the E-Servqual method found 4 (four) criteria with the negative gap value and other 16 criteria with the positive gap value. By using Cartesian diagram on the Importance Performance Analysis (IPA) method found 3 (three) priority criteria which believed as the very important criteria by the customer of PT. Pos Indonesia, however, the services given were not quite satisfactory. From 3 (three) obtained criteria, arranged based on the improvement priority level by using Potential Gain Customer Value (PGCV) method, the order were : 1) the tracking point compatibility of the most up-to-date and proper product delivery, 2) the availability of PT. Pos Indonesia website’s customer service representative website, 3) the estimation of product shipping cost listed on PT. Pos Indonesia website matches the cost to be paid.